User-Centered Design of a Wearable Gait Analysis Tool for Knee Endoprosthesis Rehabilitation - Lorenz, Katharina; Fischer, Hannah Friedrike; Wittmann, Daniela (EAI Endorsed Transactions on Pervasive Health and Technology, 2025)
With more than 193,000 cases in Germany in 2019, total knee endoprostheses (knee-TEP) are among the 20 most common surgeries performed on hospitalized patients [1]. A standard method for assessing post-operative mobility is the manual measurement of range of motion using a goniometer. This method is subjective, dependent on the clinician’s experience, and provides only a snapshot of the patient’s condition. Existing sensor-based systems for gait analysis are primarily designed for clinical use and research contexts, and are generally not intended for independent application by patients at home. To complement these solutions, we developed a mobile, wearable sensor system and a corresponding app that enables self-administered gait analysis and mobility assessment for patients with knee-TEPs in both clinical and home settings. This paper presents key insights gained from a user-centered design process employing participatory methods, highlighting implications for the development of patient centered rehabilitation technologies.
Keywords: User-centered design; Rehabilitation Tool for Patients with Knee Endoprostheses; IMU-Based wearable for Gait Analysis